An Integrated Proteomics and Metabolomics Strategy for the Mechanism of Calcium Oxalate Crystal-Induced Kidney Injury - Gao, Songyan; Chao, Yufan; Li, Na; Li, Henghui; Zhao, Hongxia; Liu, Xinru; Chen, Wei; Dong, Xin (Frontiers in Medicine, 2022)
Renal fibrosis is the pathological repair reaction of kidney to chronic injury and is the important process of chronic kidney disease progressing to end-stage renal failure. Nephrolithiasis is one of the most common renal diseases, with waist and abdomen pain, hematuria, urinary tract infection and other clinical symptoms, which can increase the risk of renal fibrosis. Oxalate crystal induced kidney injury is an early stage of nephrolithiasis; it is of great significance to explore the mechanism of which for the prevention and treatment of nephrolithiasis. A rodent model of calcium oxalate-induced crystal kidney injury was used in present study, and a network analysis method combining proteomics and metabolomics, were conducted to reveal the mechanism of crystal kidney injury and to provide potential targets for intervention of nephrolithiasis. Using the metabolomics method based on the UHPLC-Q/TOF-MS platform and the iTRAQ quantitative proteomics method, we screened a total of 244 metabolites and 886 proteins from kidney tissues that had significant changes in the Crystal group compared with that in the Control group. Then, Ingenuity pathway analysis (IPA) was applied to construct a protein-to-metabolic regulatory network by correlating and integrating the differential metabolites and proteins. The results showed that calcium oxalate (CaOx) crystal could induce inflammatory reaction and oxidative stress through Akt, ERK1/2, and P38 MAPK pathways and affect amino acid metabolism and fatty acids β oxidation, resulting in kidney injury, which provided an important direction for the early prevention and treatment of nephrolithiasis.